2013 18th International Conference on Digital Signal Processing (DSP) 2013
DOI: 10.1109/icdsp.2013.6622738
|View full text |Cite
|
Sign up to set email alerts
|

A fast matching algorithm for asymptotically optimal distributed channel assignment

Abstract: The channel assignment problem is a special case of a very well studied combinatorial optimization problem known as the assignment problem. In this paper we introduce an asymptotically optimal fully distributed algorithm for the maximum cardinality matching problem. We show that with high probability, the running time of the algorithm on random bipartite graphs is less than O N log(N) log(Np) . We then show that the proposed algorithm can be used to produce asymptotically optimal solutions for the max sum assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…The Gale-Shapley algorithm is used to solve the problem. Later in [22], a fast matching algorithm for asymptotically optimal channel assignment is proposed, which yields an asymptotically optimal matching. A similar idea is presented in [23], where a modified distributed auction algorithm is used to solve the problem, and then a faster matching algorithm is used to find the asymptotically optimal solution.…”
Section: B Matching Theory In Wireless Communicationsmentioning
confidence: 99%
“…The Gale-Shapley algorithm is used to solve the problem. Later in [22], a fast matching algorithm for asymptotically optimal channel assignment is proposed, which yields an asymptotically optimal matching. A similar idea is presented in [23], where a modified distributed auction algorithm is used to solve the problem, and then a faster matching algorithm is used to find the asymptotically optimal solution.…”
Section: B Matching Theory In Wireless Communicationsmentioning
confidence: 99%
“…In [28]- [30], a distributed channel allocation for Ad-Hoc networks was introduced, based on a carrier-sensing multiple access (CSMA) scheme and a thresholding approach for the channel gains. Although considering a different scenario, the analysis in [28]- [30] also used a random bipartite graph, albeit a very simplified one.…”
Section: A Related Workmentioning
confidence: 99%
“…In [28]- [30], a distributed channel allocation for Ad-Hoc networks was introduced, based on a carrier-sensing multiple access (CSMA) scheme and a thresholding approach for the channel gains. Although considering a different scenario, the analysis in [28]- [30] also used a random bipartite graph, albeit a very simplified one. The random bipartite graph in [28]- [30] was an Erdős-Rényi graph (i.e., existence of edges is independent), for which perfect matching existence results are well known [15].…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that the optimal solution to the channel allocation problem can be achieved using a distributed algorithm [3], [4], [5]. This algorithm is a distributed version of the auction algorithm [6] and relies on a CSMA protocol.…”
Section: Introductionmentioning
confidence: 99%